Monetary policy, economic activity and the stock market: an empirical analysis of the Kuala Lumpur Stock Exchange - Muzafar Shah Habibullah; Ahmad Zubaidi Baharumshah; Tan, Hui Boon (Penerbit Universiti Kebangsaan Malaysia, 1998)
This study attempts to answer the question whether the Kuala Lumpur Stock Exchange (KLSE) is informationally efficient with respect to both money and output. The Information Efficient Market (IEM) hypothesis is tested using the Johansen-Juselius multivariate cointegration approach. Stock prices are proxied by the Composite, Industrial, Finance, Property, Plantation and Tin indices. The measures of money supply used include the narrowly defined MI and broadly defined M2. Output is proxied by the real Gross Domestic Product (CDP). The empirical results suggest that the stock market is informationally inefficient with respect to M2 and output.